Logic and Politics of the Object in Puppet Theaters (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
The article analyzes the issue of the animated object based on the relationship it establishes with the subject who animates it and with the public. To do so, it develops a philosophical reflection on how and why the object brings meanings to the theatrical scene. Throughout the writing, concepts are evoked relevant to Plato, Husserl, Kant and Aristotle, among other philosophers and artists.
Keywords: philosophy; puppet theater; theater; theater of objects